Vaccination, Autonomy, Complexity, Solidarity - Ethical analyses of a German policy discourse. (13th November 2019) - Schröder-Bäck, P; Gille, F; Brall, C; Martakis, K; Kuhn, J
Abstract: Background: Currently, measles immunization is high on the agenda of academic and public discourses - on both sides of the Atlantic. In Germany, the discussion of mandatory (measles) immunization was intensively publicly discussed in Spring 2019. Many stakeholders, including federal politicians, plea for mandatory measles immunization. In our paper we analyse the discourse from an ethical point of view. Methods: Statements and arguments from German stakeholders in the public debate in 2019 are analysed (among them statements of the federal minister of health, the German Medical Association, NGOs and the National Ethics Council). A vaccination ethics framework and a public trust framework are applied in the analysis. Results: Politicians and other public stakeholders debate (measles) immunization and increasingly demand mandatory (measles) vaccination. However, frequently it is unclear which vaccinations or immunization programmes they refer to. They often do ignore the epidemiological situation of immunization rates in Germany, regional differences, relevant target groups and implementation mechanisms, including potential sanctions. This way they simplify the complex problem and offer (populist) simplistic solutions. Normative arguments of stakeholders repeatedly use conceptions of 'autonomy' and 'harm'; but sometimes also 'solidarity' is mentioned. Conclusions: The call for mandatory measles immunization of school and kindergarten children is offering no adequate and sufficient solution to the problem of elimination of measles. Nevertheless, it contributes to reducing infection risks for the children in care and schooling facilities. Rather, the problem has to be understood in its complexity before discussing the ethical challenges and making effective policy recommendations. When discussing ways to increase immunization rates, ethical values like public trust and solidarity have to be in the foreground - not (only) the debate of autonomy and its restriction. Key messages: In German policy discourses 2019, the discussion of "mandatory (measles) vaccination" often shows inaccuracies regarding definitions and facts. These have to be clarified before ethical analysis. Ethical issues regarding the voluntariness of measles vaccination relate also to the ethical concepts of solidarity and public trust and not only to autonomy.